Case Report: Surgical resection of giant ventricular fibroma in an infant utilizing 3D imaging guidance - Lu, Jin; Chen, Yu; Lian, Xingchen; Chang, Peipei; Wen, Ping; Zou, Na; Ma, Lin; Liu, Yuhang (Frontiers in Cardiovascular Medicine, 2025)
Primary cardiac tumors are extremely rare, with fibromas being one of the more prevalent type primary cardiac tumors in infants and children. Cardiac fibromas present a high risk of fatal arrhythmia and sudden death, hence more aggressive surgical treatment approaches are typically employed. However, certain populations, such as asymptomatic infants and young children in the early stages, require extra caution. We present the case of a patient with a giant fibroma of the heart detected during fetal development, who was followed up until the age of 5 months before undergoing surgical resection. Prior to surgery, we employed three-dimensional (3D) imaging technology to acquire a deeper understanding of the anatomical nature of cardiac tumors. We then devised a comprehensive surgical strategy to minimize the risk of damage to large blood vessels during surgery and maximize preservation of myocardial tissue. Following surgical resection of the tumor, cardiac dysfunction was managed with extracorporeal membrane oxygenation (ECMO) continuous adjuvant therapy, and conventional vasodilators such as dopamine and nitroglycerin were ad. The patient recovered well without any serious complications. This case highlights the significance of timely surgical intervention, combined with 3D imaging to develop a meticulous surgical plan and early use of ECMO to maintain cardiac function in patients with postoperative cardiac dysfunction. This can help to ensure the safety and effectiveness of giant cardiac fibromas resection in infants and young children.